THE APPLICATION OF A BALANCED SCORECARD IN SME: A CASE STUDY OF MILANZO KIDS - Sari, Asih Wulan; Alfiany, Nurvilaeli; Hesti, Azalia Novia; Nisa, Alfi Ziadatun (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2022)
The processing industry is one of the non-agricultural SMEs sectors that ranks at the top in the national economy, of which there are 14.4% of textile and convection industry players (BPS, 2015). According to a survey by the Ministry of Cooperatives and SMEs, during the Covid-19 Pandemic, the convection sector SMEs were the most affected sector with 78% of respondents claiming to have experienced a decrease in revenue and even had to close their businesses. Milanzo Kids is one of the convection SME that was established in 2013, engaged in the manufacture of children's t-shirts made of cotton and located in Jakarta, Indonesia. In 2020, Milanzo Kids experienced a decrease in revenue and profit from the previous year due to the Covid-19 pandemic. The objective of this study is to design a business development strategy using the balanced scorecard method. This research is a type of quantitative research. The data of this study were obtained from primary data through direct interviews and secondary data obtained from financial reports, journals, and books. The data processing method uses a balanced scorecard. The results of this study indicated that total omzet per year and the number of products returned per year has the highest performance, namely the final score of 0.13. While, the lowest performance indicator is the type of product produced with a final score of 0.03.